Preparation method of N-doped porous carbon material based on attapulgite and application of N-doped porous carbon material in supercapacitor

By mixing the recovered egg white with catering waste oil and concave and concave rock stone clay, and preparing N-doped porous carbon materials using a combined etching method of NaOH and dilute HF acid, the problems of low energy density of existing supercapacitors and poor conductivity of carbon materials are solved, and a high specific capacitance and environmentally friendly preparation process is achieved.

CN119601392AActive Publication Date: 2025-03-11HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411655265.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-11
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The energy density of existing supercapacitors is low, which limits their application, and the carbon materials used are poor in conductivity and are difficult to improve performance.

Method used

Using an N-doped porous carbon material based on concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave and concave

Benefits of technology

The specific capacitance in supercapacitors has been significantly improved, and the materials have the advantages of low cost, simple preparation method, and green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601392A_ABST
    Figure CN119601392A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical energy storage, and discloses a preparation method of an N-doped porous carbon material based on attapulgite and application of the N-doped porous carbon material in a supercapacitor, and the preparation method comprises the following steps: uniformly mixing recovered egg white with waste cooking oil, adding attapulgite clay, uniformly stirring, and standing; heating and carbonizing under the protection of nitrogen to obtain black powder; mixing the black powder with a NaOH solution, and carrying out heating treatment, suction filtration, water washing and drying to obtain an alkali etching carbon material; and placing the alkali-etched carbon material in the dilute HF solution, carrying out suction filtration, washing with water, and drying to obtain the N-doped porous carbon material. The attapulgite crystal is used as a porous material template, the waste cooking oil and the recycled egg white are used as a carbon source and a nitrogen element source, the attapulgite crystal, the waste cooking oil and the recycled egg white are mixed and then subjected to carbonization-alkali-acid combined etching to prepare the N-doped porous carbon material, and the N-doped porous carbon material is used for a supercapacitor, shows excellent specific capacitance and has the advantages of being low in cost, simple in preparation method and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy storage technology, and in particular to a method for preparing an N-doped porous carbon material based on attapulgite and an application thereof in a supercapacitor, and specifically to a method for preparing an N-doped porous carbon supercapacitor material based on attapulgite clay, waste cooking oil, and recycled egg white and an application thereof. Background Art

[0002] Supercapacitors have the advantages of high power density, short charging time, long service life, and green environmental protection, and therefore have attracted widespread attention. However, their energy density is relatively low, which limits their application. In order to improve the performance of supercapacitors, porous carbon materials with high specific surface area, excellent specific capacitance and high specific charge have received increasing attention. The currently used carbon materials are mostly synthesized from petroleum coke and biomass (CN115642039A), and there are a large number of micropores. These disordered pore structures lead to poor conductivity of carbon materials, limiting the improvement of their performance. The introduction of nitrogen can improve the conductivity of carbon materials and the corresponding overall capacity of the material (CN115708179A).

[0003] Attapulgite clay is a one-dimensional natural porous inorganic crystal. By using biomass sucrose or furfuryl alcohol as a loading material and then carbonizing and etching to remove the template, porous carbon nanotubes with a high specific surface area can be obtained, which show good battery performance. Waste cooking oil and recycled egg white are wastes from the catering and food processing fields. Carbonization of waste cooking oil can generate carbon materials. 90% of the solid solution in egg white is protein, and the nitrogen content is about 16%. It can be used as a doping component to dope carbon materials and be carbonized into carbon materials at the same time. Summary of the invention

[0004] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a method for preparing N-doped porous carbon materials based on attapulgite and their application in supercapacitors. Attapulgite crystals are used as porous material templates, and waste cooking oil and recycled egg whites are used as carbon sources and nitrogen sources. The three are mixed and then subjected to carbonization-alkali-acid combined etching to prepare N-doped porous carbon materials for supercapacitors, which show excellent specific capacitance and have the advantages of low cost, simple preparation method, and green environmental protection.

[0005] Technical solution: On the one hand, the present invention provides a method for preparing an N-doped porous carbon material based on attapulgite, comprising the following steps: S1: Mix the recycled egg white and the waste cooking oil evenly to obtain a mixed solution; add attapulgite clay to the mixed solution, stir evenly, and let stand; then heat to 600-800°C under nitrogen protection for carbonization for 2-3 h to obtain a black powder; S2: mixing the black powder with a NaOH solution, heating the mixture at 100-180° C. for 5-10 h, filtering, washing with water, and drying the mixture to obtain an alkali-etched carbon material; S3: placing the alkali-etched carbon material in the dilute HF solution, stirring, filtering, washing with water, and drying to obtain an attapulgite-based N-doped porous carbon material.

[0006] Furthermore, in S1, the mass ratio of the recovered egg white to the waste catering oil is 1:1-4.

[0007] Furthermore, in S1, the solid-liquid mass ratio of the attapulgite clay to the mixed liquid is 1:1-2.

[0008] Furthermore, in S1, the standing time is 5-6 h.

[0009] Furthermore, in S2, the solid-liquid mass ratio of the black powder to the NaOH solution is 20%.

[0010] Furthermore, the concentration of the NaOH solution is 2.5-4 mol / L.

[0011] Furthermore, in S2, the alkaline solution obtained by filtration can be recycled and used for synthesizing zeolite, white carbon black, etc.

[0012] Furthermore, in S3, the solid-liquid ratio of the alkali-etched carbon material to the dilute HF solution is 20%.

[0013] Furthermore, the concentration of the dilute HF solution is 5-10%.

[0014] Preferably, in S3, the stirring time is 2 to 3 h.

[0015] On the other hand, the present invention provides an application of an N-doped porous carbon material based on attapulgite prepared by any of the methods described above in a supercapacitor.

[0016] The synthesis principle of the present invention is as follows: waste oil and recycled egg white are mixed evenly, added to attapulgite clay, the liquid mixture enters the internal pores of attapulgite, covers the surface of attapulgite fiber, and is carbonized under nitrogen protection to form a carbon material. At the same time, the N element of egg white protein dopes the carbon element, and the silicon and aluminum components in attapulgite can be dissolved by heating with NaOH solution. The residual mineral components and the associated quartz stable to alkali can be dissolved and removed by dilute HF acid to obtain N-doped porous carbon material, which is used as an electrode material for supercapacitors. After the porous attapulgite template is removed, the obtained carbon material has a hollow porous structure. The electrode performance of the material is improved due to the introduction of N doping from egg white protein. Alkali-dilute HF acid combined etching not only recovers most of the mineral components, but also completely removes the residues to obtain a relatively pure carbon material, avoiding the problem of a large amount of waste liquid to be treated after direct HF etching. The raw materials are mainly natural minerals and recycled materials, with low cost and green and environmentally friendly preparation process.

[0017] Beneficial effects: The present invention uses cheap clay minerals as templates and waste from the catering and food processing fields as carbon sources to prepare N-doped porous carbon super electrical materials. Combined with green etching methods, it can achieve economical and green preparation of N-doped porous carbon materials. Compared with the prior art, the specific beneficial effects are as follows: Waste cooking oil and recycled egg white can be used as supercapacitor electrode materials after high-temperature carbonization. The price is low and waste can be reused. At the same time, the carbonization of egg white into carbon material can also provide N element to modify and dope the carbon material. A mixture of waste cooking oil and recycled egg white infiltrates into the pores of attapulgite, where it is carbonized into carbon material after high-temperature curing. After etching away the mineral template, the resulting carbon material replicates the porous structure of the mineral, which is conducive to the storage of metallic sodium ions. The alkaline solution obtained by alkali etching of attapulgite can be recycled and used to synthesize zeolite, white carbon black and other products; however, when only HF acid etching is used, the etching solution is difficult to recover; when only alkali etching is used, it is difficult to completely remove attapulgite and impure quartz. Through alkali-HF acid combined etching, not only the mineral components are recovered, but also the HF acid concentration used is low and can be used for a long time, the HF utilization rate is improved, it is green and economical, and more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 is the XRD spectrum of the N-doped porous carbon material prepared in Embodiment 1 of the present invention; Figure 2 This is a SEM photograph of the N-doped porous carbon material prepared in Embodiment 1 of the present invention; Figure 3 The electrode performance of the N-doped porous carbon material prepared in Embodiment 1 of the present invention. DETAILED DESCRIPTION

[0019] The present invention is described in detail below in conjunction with the embodiments.

[0020] Implementation 1: The recycled egg white and catering waste oil were mixed evenly in a mass ratio of 1:1, and then attapulgite clay was added in a solid-liquid mass ratio of 1:1, stirred evenly, allowed to stand for 5 hours, transferred to a porcelain crucible, and heated to 700°C for carbonization for 2 hours under nitrogen protection to obtain a black powder; the black powder was added to a 2.5 mol / L NaOH solution at a solid-liquid mass ratio of 20%, transferred to a reactor, heated at 180°C for 5 hours, alkali-etched to remove the attapulgite mineral components, filtered, washed with water, and dried to obtain an alkali-etched carbon material (the alkaline solution obtained by filtration can be recycled and used to synthesize zeolite, white carbon black and other products); the alkali-etched carbon material was transferred to a 5% dilute HF solution at a solid-liquid mass ratio of 20%, stirred for 3 hours, and the residual mineral components and impurity quartz were further removed. The mixture was filtered, washed with water, and dried to obtain an N-doped porous carbon material.

[0021] Figure 1 This is the XRD spectrum of N-doped porous carbon material. It can be seen that the characteristic peak of attapulgite disappears, and a mantou peak appears in the range of 2θ of 20-30°, indicating that it is an amorphous carbon material; the characteristic peak that appears at 2θ of 43° is the characteristic peak of graphitized carbon material. In addition, a small amount of quartz peak remains in the material. Figure 2 This is the SEM photo of the N-doped porous carbon material. It can be seen that the carbon material still maintains the morphology of attapulgite fibers. Figure 3 In order to prepare it as the electrode performance of capacitor electrode material, its specific capacitance is 338.8F / g at a current density of 0.5 A / g. In comparison, the specific capacitance of the carbon material obtained by alkali etching alone is 143 F / g, the specific capacitance of the carbon material obtained by HF etching alone is 238 F / g, and the specific capacitance of the carbon material obtained by alkali-HF combined etching is 308 F / g. After the introduction of N element, the specific capacitance of N-doped porous carbon increased to 339 F / g, indicating that it has good application prospects in supercapacitors.

[0022] Implementation 2: The recycled egg white and catering waste oil were mixed evenly at a mass ratio of 1:2, and then attapulgite clay was added at a solid-liquid mass ratio of 1:1.2, stirred evenly, allowed to stand for 5 hours, transferred to a porcelain crucible, and heated to 600°C for carbonization for 3 hours under nitrogen protection to obtain a black powder; the black powder was added to a 3 mol / L NaOH solution at a solid-liquid mass ratio of 20%, transferred to a reactor, heated at 150°C for 6 hours, alkali-etched to remove the attapulgite mineral components, filtered, washed with water, and dried to obtain an alkali-etched carbon material (the alkaline solution obtained by filtration can be recycled and used to synthesize zeolite, white carbon black and other products); the alkali-etched carbon material was transferred to a 6% dilute HF solution at a solid-liquid mass ratio of 20%, stirred for 2.5 hours, and the residual mineral components and impurity quartz were further removed. The mixture was filtered, washed with water, and dried to obtain an N-doped porous carbon material with a specific capacitance of 328 F / g.

[0023] Implementation 3: The recycled egg white and catering waste oil were mixed evenly at a mass ratio of 1:3, and then attapulgite clay was added at a solid-liquid mass ratio of 1:1.5, stirred evenly, allowed to stand for 5 hours, transferred to a porcelain crucible, and heated to 750°C for carbonization for 2.5 hours under nitrogen protection to obtain a black powder; the black powder was added to a 3.5 mol / L NaOH solution at a solid-liquid mass ratio of 20%, transferred to a reactor, heated at 120°C for 8 hours, alkali-etched to remove the attapulgite mineral components, filtered, washed with water, and dried to obtain an alkali-etched carbon material (the alkaline solution obtained by filtration can be recycled and used to synthesize zeolite, white carbon black and other products); the alkali-etched carbon material was transferred to an 8% dilute HF solution at a solid-liquid mass ratio of 20%, stirred for 2.5 hours, and the residual mineral components and impurity quartz were further removed. The black powder was filtered, washed with water, and dried to obtain an N-doped porous carbon material with a specific capacitance of 315 F / g.

[0024] Implementation 4: The recycled egg white and catering waste oil were mixed evenly at a mass ratio of 1:4, and then attapulgite clay was added at a solid-liquid mass ratio of 1:2, stirred evenly, allowed to stand for 5 hours, transferred to a porcelain crucible, and heated to 800°C for carbonization for 2 hours under nitrogen protection to obtain a black powder; the black powder was added to a 4 mol / L NaOH solution at a solid-liquid mass ratio of 20%, transferred to a reactor, heated at 100°C for 10 hours, alkali-etched to remove the attapulgite mineral components, filtered, washed with water, and dried to obtain an alkali-etched carbon material (the alkaline solution obtained by filtration can be recycled and used to synthesize zeolite, white carbon black and other products); the alkali-etched carbon material was transferred to a 10% dilute HF solution at a solid-liquid mass ratio of 20%, stirred for 2 hours, and the residual mineral components and impurity quartz were further removed. The black powder was filtered, washed with water, and dried to obtain an N-doped porous carbon material with a specific capacitance of 308 F / g.

[0025] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an N-doped porous carbon material based on attapulgite, characterized in that: The following steps are involved: S1: Mix the recycled egg white and the waste cooking oil evenly to obtain a mixed solution; add attapulgite clay to the mixed solution, stir evenly, and let stand; then heat to 600-800°C under nitrogen protection for carbonization for 2-3 h to obtain a black powder; S2: mixing the black powder with a NaOH solution, heating the mixture at 100-180° C. for 5-10 h, filtering, washing with water, and drying the mixture to obtain an alkali-etched carbon material; S3: placing the alkali-etched carbon material in the dilute HF solution, stirring, filtering, washing with water, and drying to obtain an attapulgite-based N-doped porous carbon material.

2. The method for preparing an N-doped porous carbon material based on attapulgite according to claim 1, characterized in that: In S1, the mass ratio of the recovered egg white to the waste cooking oil is 1:1-4; In S1, the solid-liquid mass ratio of the attapulgite clay to the mixed solution is 1:1-2.

3. The method for preparing an N-doped porous carbon material based on attapulgite according to claim 1, characterized in that: In S1, the standing time is 5-6 h.

4. The method for preparing an N-doped porous carbon material based on attapulgite according to claim 1, characterized in that: In S2, the solid-to-liquid mass ratio of the black powder to the NaOH solution is 20%.

5. The method for preparing the N-doped porous carbon material based on attapulgite according to claim 4, characterized in that: The concentration of the NaOH solution is 2.5-4 mol / L.

6. The method for preparing an N-doped porous carbon material based on attapulgite according to claim 1, characterized in that: In S2, the alkaline solution obtained by filtration can be recycled and used for synthesizing zeolite, white carbon black, etc.

7. The method for preparing an N-doped porous carbon material based on attapulgite according to claim 1, characterized in that: In S3, the solid-to-liquid ratio of the alkali-etched carbon material to the dilute HF solution is 20%.

8. The method for preparing the N-doped porous carbon material based on attapulgite according to claim 7, characterized in that: The concentration of the dilute HF solution is 5-10%.

9. The method for preparing the N-doped porous carbon material based on attapulgite according to claim 1, characterized in that: In S3, the stirring time is 2 to 3 h.

10. Use of the N-doped porous carbon material based on attapulgite prepared according to the method according to any one of claims 1 to 9 in supercapacitors.

Citation Information

Patent Citations

  • Preparation method of nitrogen and phosphorus co-doped eucalyptus bark porous carbon supercapacitor electrode material

    CN115642039A

  • Nitrogen-doped porous nano carbon material, capacitor electrode material, capacitor electrode and preparation method thereof, and supercapacitor

    CN115708179A

  • Preparation method of high-efficiency composite attapulgite / rice hull activated carbon purified water material

    CN103301807A

  • Preparation method and application of heterogeneous doping graded porous carbon supercapacitor electrode material

    CN107117595A

  • Preparation method and application of binary composite porous carbon material

    CN116654894A